PP31 Fertility Rates in Women with Inflammatory Bowel Disease Compared with the General Female Population: A United Kingdom Population-Based Cohort Study. (10th September 2013) - Ban, L; Tata, I J; Fiaschi, L; Card, T
Abstract : Background: Previous studies have raised concerns about reduced fertility in women diagnosed with inflammatory bowel disease (IBD). Our objectives were to compare estimates of age-specific fertility rates in women with and without IBD and to assess whether relative fertility was different before and after clinical diagnoses in comparison with the general female population. Methods: We included all women aged 15 to 44 years between 1990 and 2010 from a large United Kingdom primary care database. Women with IBD were defined as those with a clinically diagnosed IBD in their medical records. Each woman was assigned an IBD diagnosis date corresponding to the date of the first record of IBD or the date of the first prescription of 5-aminosalicylic acid (excluding sulfasalazine) if this was before the first diagnostic recording. We estimated overall and age-specific fertility rates by 5-year age bands as the number of live births per 1000 person-years for all women with IBD and separately during the time before and after first clinical recognition, using Poisson regression to compare rates in women without IBD in the general population. Maternal smoking and socioeconomic status were added into the univariate model one at a time and variables that changed the magnitude of the fertility rate ratios by at least 10% were retained in the final model. We also calculated fertility rates for women with Crohn's disease (CD) and ulcerative colitis (UC) separately. Results: Fertility rates were 46.2 (95% CI 44.6, 47.9) and 49.3 (49.2, 49.5) live births per 1000 person-years in 9, 639 women with IBD and 2, 131, 864 without IBD, respectively (rate ratio [RR] 0.94 [0.90, 0.97]). Age-specific fertility rates showed that the lower fertility rates in women with IBD were restricted to the 15-24 and 35-44 year age groups. Fertility rates were low in women with IBD after diagnosis (RRs compared with women never clinically diagnosed with IBD 0.88 [0.84, 0.93], 0.91 [0.85, 0.98] and 0.85 [0.79, 0.93] for IBD overall, CD and UC respectively), but not before. Conclusion: Compared with women in the general population, women with IBD have decreased fertility especially after they are clinically diagnosed. Gastroenterologists and obstetricians should be aware of women's fertility plan and are advised to communicate this information to women with IBD.